A chaotic outlook on biological systems. (February 2017) - Scharf, Yael
Highlights: A new way to use the chaos theory in biology is put forward. Development, cancer and evolution connections and biophysical analyses are suggested in means of mapping and extrapolation. Genetical-biophysical aspects are used in order to evaluate the connection of mitochondria and the nucleus. Abstract: Biological systems such as the cell are mostly analyzed by looking at the biophysical properties of their inner workers, such as proteins. However, some have suggested that biological systems have quantum properties in addition to their physical complexities. Thus, these systems can be measured by the displacement and geometry or the velocity of the acting agents inside them. In this paper I suggest that measurement of displacement or of biophysical properties does not suffice when calculating the dynamics of the system, and vice versa. Furthermore, I propose a theoretical background to approach and measure the dynamics of biological systems by using the chaos theory as means of calculation. This approach will be exemplified in evolution, development and cancer with a strong emphasis on endosymbiosis of the mitochondria and the cell in genetic aspects.